2022
DOI: 10.3390/cancers14010219
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Post-Translational Regulation of p53 in Colorectal Cancer by Exploiting Vulnerabilities in the p53-MDM2 Axis

Abstract: The role played by the key tumor suppressor gene p53 and the implications of p53 mutations for the development and progression of neoplasia continue to expand. This review focuses on colorectal cancer and the regulators of p53 expression and activity identified over the past decade. These newly recognized regulatory mechanisms include (1) direct regulation of mouse double minute 2 homolog (MDM2), an E3 ubiquitin-protein ligase; (2) modulation of the MDM2-p53 interaction; (3) MDM2-independent p53 degradation; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 117 publications
(133 reference statements)
0
3
0
Order By: Relevance
“…We note that variations on E17 in human p53 are cancer mutants, frequently associated with female genital cancers ( Petitjean et al 2007 ; Ganguly and Chen 2015 ). The K24N mutation found in colorectal cancers, is thought to implicate ubiquitination by TRAF6, thereby facilitating p53 acetylation by p300 ( Lai et al 2022 ). Isothermal titration calorimetry measurements demonstrated that this structural variation did not prevent the binding affinity for p53TAD–MDM2 ( Zhan et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We note that variations on E17 in human p53 are cancer mutants, frequently associated with female genital cancers ( Petitjean et al 2007 ; Ganguly and Chen 2015 ). The K24N mutation found in colorectal cancers, is thought to implicate ubiquitination by TRAF6, thereby facilitating p53 acetylation by p300 ( Lai et al 2022 ). Isothermal titration calorimetry measurements demonstrated that this structural variation did not prevent the binding affinity for p53TAD–MDM2 ( Zhan et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…MDM2, a key downstream protein of Akt, can be phosphorylated by p-Akt. p-MDM2 can translocate to the nucleus and modulate p53 levels by targeting p53 for protein degradation ( 42 ). Therefore, the Akt/MDM2/p53 signaling pathway serves a key role in regulation of the cell cycle, proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Global data show that colorectal cancer (CRC) has the third highest incidence, followed by breast and lung cancer 1 . CRC can occur as small, benign polyps inside the colon, which subsequently become malignant 2 .…”
Section: Introductionmentioning
confidence: 99%